METODE DAN TEKNIK PEMBELAJARAN PELATIHAN MENJAHIT PADA WARGA BELAJAR HETEROGEN DI UPTD PELATIHAN KERJA KOTA BENGKULU - Tiara Priz Erizah; Agus Zainal Rachmat; Bayu Pradikto (Jurnal Pendidikan Sepanjang Hayat, 2020)
This research was descriptive qualitative research aimed to describe the sewing training implementation for heterogeneous learning citizens methods and techniques of learning. Participants in this study were heads of administrative sub-sections, instructors and sewing training citizens learning. This research was conducted at UPTD Bengkulu Work Training on 10 to 31 March 2020. Data collection was carried out through interviews, observations and documentation. The data were analyzed and validated using triangulation data validity technique. From research results, the sewing training instructors apply lecture learning methods, question and answer learning methods, discussion learning methods, demonstration learning methods, group teaching learning methods and individual teaching learning methods. The instructional methods applied by instructors to heterogeneous learning citizens was different, namely by applying group teaching methods with participatory coaching learning techniques. Keywords: sewing training, learning citizens, heterogeneous.